2019
DOI: 10.1021/acsabm.8b00805
|View full text |Cite
|
Sign up to set email alerts
|

Nanoengineering of Crystal and Amorphous Surfaces of Pharmaceutical Particles for Biomedical Applications

Abstract: The morphology, size and surface properties of pharmaceutical particles form an essential role in the therapeutic performance of active pharmaceutical ingredients (APIs) and excipients as constituents in various drug delivery systems and clinical applications. Recent advances in methods for surface modification, however, rely heavily on liquid-phase based modification processes and afford limited control over the thickness and conformality of the coating. Atomic layer deposition (ALD), on the other hand, enabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…Atomic layer deposition (ALD) is a vapor-phase technique for depositing ultrathin conformal films on any substrate with thickness control at the sub-nanometer level. , Alternating exposures of a precursor and a co-reactant in the vapor phase separated by purging steps enable self-terminating reactions with the substrate surface, thus resulting in an atomically controlled film growth. Widely used for the functionalization of wafers in the semiconductor industry with oxide ceramic films, ALD has also been applied to a large variety of powders, recently also including pharmaceutical particles, due to its ability to conformally coat complex three-dimensional substrates. Crucially, nanophase ceramics have already been used in a broad spectrum of biomedical and drug delivery applications, as they can modulate drug release kinetics, incorporate multifunctional molecules, and target action sites . ALD of oxide ceramics can therefore extend release and improve flow properties and solid-state stability of virtually any pharmaceutical substance. , Nanoscale oxide ceramic ALD films have been shown to slow down the dissolution rate of acetaminophen particles, while preventing drug chemical degradation and cytotoxicity .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atomic layer deposition (ALD) is a vapor-phase technique for depositing ultrathin conformal films on any substrate with thickness control at the sub-nanometer level. , Alternating exposures of a precursor and a co-reactant in the vapor phase separated by purging steps enable self-terminating reactions with the substrate surface, thus resulting in an atomically controlled film growth. Widely used for the functionalization of wafers in the semiconductor industry with oxide ceramic films, ALD has also been applied to a large variety of powders, recently also including pharmaceutical particles, due to its ability to conformally coat complex three-dimensional substrates. Crucially, nanophase ceramics have already been used in a broad spectrum of biomedical and drug delivery applications, as they can modulate drug release kinetics, incorporate multifunctional molecules, and target action sites . ALD of oxide ceramics can therefore extend release and improve flow properties and solid-state stability of virtually any pharmaceutical substance. , Nanoscale oxide ceramic ALD films have been shown to slow down the dissolution rate of acetaminophen particles, while preventing drug chemical degradation and cytotoxicity .…”
Section: Introductionmentioning
confidence: 99%
“…Widely used for the functionalization of wafers in the semiconductor industry with oxide ceramic films, ALD has also been applied to a large variety of powders, recently also including pharmaceutical particles, due to its ability to conformally coat complex three-dimensional substrates. Crucially, nanophase ceramics have already been used in a broad spectrum of biomedical and drug delivery applications, as they can modulate drug release kinetics, incorporate multifunctional molecules, and target action sites . ALD of oxide ceramics can therefore extend release and improve flow properties and solid-state stability of virtually any pharmaceutical substance. , Nanoscale oxide ceramic ALD films have been shown to slow down the dissolution rate of acetaminophen particles, while preventing drug chemical degradation and cytotoxicity . Similarly, we have demonstrated that nanosized Al 2 O 3 -based films grown via ALD in a fluidized bed reactor at nearly ambient conditions can greatly sustain the release and improve the dispersibility of budesonide and lactose particles. , In addition, Al 2 O 3 ALD films with a thickness of 30–35 nm have been proven to maintain a stable plasma concentration for indomethacin, when administered subcutaneously in rats, up to over 12 weeks .…”
Section: Introductionmentioning
confidence: 99%
“…The thickness of the PET film (t P ET ) resulting from the PET wt. % (x P ET ) was calculated according to the equation described by Zhang et al (36) correlating the mass fraction and the thickness of the deposited material, assuming a TiO 2 particle diameter (d TiO 2 ) of 32.7 nm (d 3,2 ) (37), a TiO 2 density (ρ TiO 2 ) of 4.23 g/cm 3 and a PET density (ρ P ET ) of 1.38 g/cm 3 , typical of bulk PET (Eq. (2)):…”
Section: Mld Cyclementioning
confidence: 99%
“…Moreover, investigating which conditions ensure a good fluidization quality for low‐micron‐sized pharmaceutical powders is relevant for their handling in coating processes such as atomic layer deposition. [ 27,28 ]…”
Section: Introductionmentioning
confidence: 99%